A philatelic history of anesthesiology - K C Sekhar (Wolters Kluwer Medknow Publications, 2013)
Thematic or topical philately deals with stamp collection based on a particular topic or theme. This article deals with a thematic depiction of the history of anesthesia from ancient to modern times using stamps, postal stationery and cancellations.